Autoimmune skin and connective tissue diseases and risk of venous thromboembolism: a population‐based case‐control study - JOHANNESDOTTIR, S. A.; SCHMIDT, M.; HORVÁTH‐PUHÓ, E.; SØRENSEN, H. T. (Journal of thrombosis and haemostasis, 2012)
Background:  Systemic inflammation is associated with vessel wall damage, upregulation of procoagulants, downregulation of anticoagulants, and suppression of fibrinolysis. Autoimmune diseases may therefore increase the risk of venous thromboembolism (VTE). Objectives:  To examine whether autoimmune skin and connective tissue diseases are associated with increased VTE risk. Methods:  We conducted this population‐based case–control study in northern Denmark, using administrative databases. From 1999 to 2009, we identified 14 721 VTE cases and 147 210 birth year‐matched, sex‐matched and county‐matched population controls. The date of diagnosis/matching was considered to be the index date for cases and controls. For all study subjects, we identified hospital diagnoses of autoimmune skin or connective tissue diseases between 1977 and the index date. We used conditional logistic regression with adjustment for VTE risk factors to calculate odds ratios and 95% confidence intervals (CIs) for patients with vs. without autoimmune disease. Given the risk‐set sampling design, odds ratios estimate incidence rate ratios (IRRs). Results:  Autoimmune skin disease was not associated with VTE (IRR 1.0; 95% CI 0.9–1.2). Patients with connective tissue disease had an increased VTE risk within 90 days (IRR 2.3; 95% CI 1.5–3.7) and 91–365 days (IRR 2.0; 95% CI 1.5–2.8) after diagnosis, but not thereafter (IRR 1.1; 95% CI 1.0–1.2). Among connective tissue diseases, the greatest overall risk increases were found for juvenile rheumatoid arthritis (IRR 3.0; 95% CI 1.4–6.4) and systemic lupus erythematosus (IRR 2.8; 95% CI 1.7–4.7). Conclusions:  Autoimmune connective tissue disease was associated with an increased risk of VTE within 1 year after diagnosis, whereas skin diseases were not.